Download presentation

Presentation is loading. Please wait.

Published byDonna Fleming Modified over 6 years ago

1
Objective The student will be able to: solve equations using addition and subtraction.

2
1) Solve r + 16 = -7 Think of this equation as a balance scale. Whatever you do to one side has to be done to the other to keep it balanced!

3
1) Solve r + 16 = -7 To solve, you must get the variable by itself. What number is on the same side as r? 16 To get r by itself, we must undo the “add 16”. What is the opposite of addition? Subtract 16

4
- 16 -16 r = -23 -23 + 16 = -7 1) Solve r + 16 = -7 1.Draw “the river” to separate the equation into 2 sides 2.Subtract 16 from both sides 3.Simplify vertically 4.Check your answer by substituting your answer back into the problem

5
2) Solve x + 2 = -3 Get the variable by itself. What is your first step? 1.Add 2 to both sides 2.Subtract 2 from both sides 3.Add 3 to both sides 4.Subtract 3 from both sides Answer Now

6
2) Solve x + 2 = -3 - 2 - 2 x = -5 -5 + 2 = -3 1.Draw “the river” to separate the equation into 2 sides 2.Subtract 2 from both sides 3.Simplify vertically 4.Check your answer by substituting your answer back into the problem On homework and tests, be sure to check your work!! There is no reason why you should miss a problem!

7
3) Solve 8 = m - 3 1.m = 5 2.m = 11 3.m = 24 4.m = 8/3 Answer Now

8
3) Solve 8 = m - 3 + 3+ 3 11= m 8 = 11 - 3 1.Draw “the river” to separate the equation into 2 sides 2.Add 3 to both sides 3.Simplify vertically 4.Check your answer by substituting your answer back into the problem

9
When solving equations, we want to eliminate double signs. y + (-3) = 8 is rewritten as y – 3 = 8 p – (-5) = 6 is rewritten as p + 5 = 6 As a general rule, replace “+ (- )” with “–” and “– (- )” with “+”. This will make things less confusing in the future!

10
4) Solve y + (-3) = 7 y – 3 = 7 + 3 +3 y = 10 10 + (-3) = 7 1.Draw “the river” to separate the equation into 2 sides 2.Eliminate the double sign 3.Add 3 to both sides 4.Simplify vertically 5.Check your answer by substituting your answer back into the problem

11
5) Solve. -x - (-2) = 1 -x + 2 = 1 - 2 - 2 -x = -1 x = 1 -(1) + 2 = 1 1.Draw “the river” to separate the equation into 2 sides 2.Eliminate the double sign 3.Subtract 2 from both sides 4.Simplify vertically 5.We haven’t gotten x by itself. If we read this aloud, it is “the opposite of x equals -1”. What would x be equal? 6.Check your answer

12
Solve -y – (-3) = 7 1.y = 10 2.y = 4 3.y = -10 4.y = -4 Answer Now

13
Try the following on your paper. X - 7 = -1 X - 4 = 66 8 = X - 2 -8 = X - 2

14
1. C + 3 = 5 Variable Mark the variable then leave it alone. Move everything away from the variable. - 3 C = 2 2. m - 3 = 5 +3 = 8 m Variable

15
3. P + (-12) = -5 “fix” double signs first P – 12 = -5 +12 P= 7 4. Y - (-6) = 3 Y + 6 = 3 - 6 Y= -3 “fix” double signs first

16
6. X – (-28) = - 48 X + 28 = - 48 - 28 X = - 76

Similar presentations

© 2022 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google